2016
DOI: 10.1016/j.neulet.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Depressed basal hypothalamic neuronal activity in type-1 diabetic mice is correlated with proinflammatory secretion of HMBG1

Abstract: We recently found indicators of hypothalamic inflammation and neurodegeneration linked to the loss of neuroprotective factors including insulin-like growth factor (IGF-1) and IGF binding protein-2 (IGFBP-3) in mice made diabetic using streptozotocin (STZ). In the current work, a genetic model of type-1 diabetes (Ins2Akita mouse) was used to evaluate changes in neuronal activity and concomitant changes in the proinflammatory mediator high-mobility group box-1 (HMBG1). We found basal hypothalamic neuronal activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Manganese-enhanced magnetic resonance (MEMRI) is a very powerful experimental technique that provides a novel approach for examining in vivo neuronal activity in chronic disease models (Yu et al, 2005 ; Kimura et al, 2007 ; Perez et al, 2013 ; Zubcevic et al, 2014 ; Thinschmidt et al, 2016 ). The experimental design was performed as previously described (Zubcevic et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese-enhanced magnetic resonance (MEMRI) is a very powerful experimental technique that provides a novel approach for examining in vivo neuronal activity in chronic disease models (Yu et al, 2005 ; Kimura et al, 2007 ; Perez et al, 2013 ; Zubcevic et al, 2014 ; Thinschmidt et al, 2016 ). The experimental design was performed as previously described (Zubcevic et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Scans were aligned with a segmented atlas of the rat brain using an automated affine linear registration tool from FMRIB software library ( flirt program in FSL, Oxford University). We used a voxel-wise signal normalization procedure as previously published (Perez et al, 2013 ; Zubcevic et al, 2014 ; Thinschmidt et al, 2016 ). Image processing was carried out using itk SNAP ( http://www.itksnap.org ) and Matlab custom code.…”
Section: Methodsmentioning
confidence: 99%
“…An imbalance in the sympathetic nervous system, with the loss of parasympathetic drive and increased sympathetic activation, occurs in diabetes. Ultimately these neuronal changes transition to neuronal loss and in the bone marrow can directly impact diabetic retinopathy [16, 17, 27, 28, 30, 37, 38, 47-50]. In chronic diabetes bone marrow denervation occurs and precedes the onset of diabetic retinopathy in rodent models of diabetes [28, 30, 37, 49].…”
Section: The Bone Marrow- Brain Connection In the Pathogenesis Of Diamentioning
confidence: 99%
“…In addition, MEMRI is also used to detect changes in neuronal activity caused by neuroinflammation in metabolic diseases. Thinschmidt et al found a significant reduction in basal hypothalamic neuronal activity in 8-month-old Ins2 Akita diabetic mice using MEMRI (175).…”
Section: Neuroinflammation and Drug Abusementioning
confidence: 99%